Investigar sobre la actividad educativa: trascendencia en la formación de los docentes. - E. González Jiménez, Félix (Revista Complutense de Educación, 2006)
The research is inescapable in the educational activity; it must be component basic of the formation of the teaching staff. The investigating activity of the educational ones is singular. How it is responded to that necessity and singularity is the assignment of this article.